Trends of Problems with Functioning in Everyday Life for Children Post Brain Tumor Treatment: As Documented in Professional Records. - Björklund, A-C.; Coci, A–I.; Granlund, M; Santacroce, S.J.; Darcy, L.; Augustine, L.; Björk, M. (Comprehensive Child & Adolescent Nursing, 2025)
Background: Children who complete brain tumor treatment encounter ongoing problems with functioning that fluctuate over time. Previous studies shows that health care and schools tend to focus more on the child's cancer-related body symptoms, rather than on existing problems to participate and manage everyday life activities, or moreover of environmental barriers they face. Few studies address how the child's problems to function on body, activity and participation levels co-occur and are presented over time. Therefore, this study´s purpose is to describe how documented problems with functioning, vary over time in children who have completed brain tumor treatment. Methods: Medical and school records from seven children were reviewed for up to 5 years after treatment completion, to identify problems and link these to International Classification of Functioning, Disability and Health (ICF) code domains. The coded data were divided into six-month blocks over a 4-year time period, analyzed statistically and illustrated graphically. Code variations on group-levels and patterns of body, activity and environmental codes that tentatively co-occurred with participation were exemplified in a child-case, using a collaborative problem-solving (CPS) approach. Results: Based on median (Md) number of codes within participation, activity, body and environment, the children exhibited ongoing problems with body function over time (Md 11–18). Activity-related problems were most noticeable about 1-year post-treatment completion (Md 6), and participation problems (Md 1–2) persisted throughout the follow-up period. Documentation of environmental problems was limited but increased after 3 years (Md 3). In the child-case example, participation problems with self-care, schooling and peer-relations continued across the years, with plausible explanations related to problems with communication and fine-hand function (activity), fatigue (body function) and with surrounding supportive systems (environment). Conclusion: Over time, professionals' documentation predominantly focused on problems with the child's body function, while functioning in everyday life and environmental barriers affecting participation, was often neglected. By using the ICF and CPS, service professionals, including nurses, are provided with guidance for comprehensive and systematic approach of addressing patterns of co-occurring problems with functioning, which could lead to improved support to optimize the child's participation in everyday life.